A Study on Interleave Division Multiple Access - Shah, Chirag R (Edelweiss Applied Science and Technology, 2018)
As wireless broadband communication has been experiencing a tremendous growth in past few year, the demands for various new & advanced multiple access techniques is increasing consistently. We can experience many new multiple access techniques in 3G & 4G. Here in this article we propose the multiple access technique IDMA which was developed with the view of achieving something more in terms of speed and capacity then what we had in 3G. The most important in IDMA is turbo-code which has increased the efficiency of 4G to a larger extent. By using these turbo codes with interleave division multiple excess the data rates 4G technology has been increased significantly. The basic idea behind this article is to lead down how by using interleaver division multiple accesses we can achieve higher coding gain, capacity, high speed (both for uploading & downloading) by using turbo codes along with IDMA.